Dynamic Stability of Aerostat-Drone - Md Said, Mohd Shahruddin (Universiti Teknologi PETRONAS, 2016)
The current generation of drone lack extended hovering and flight capabilities. Equipping a drone with an inflatable structure such as aerostat can enhances endurance as aerostat can enhance the flight duration of the drone by using the buoyant force from gas. However, adding the aerostat to the drone can affect the stability of the drone and lead to less control performance of the drone. In this project, an experiment was conducted to test the effect of the aerostat on the drone stability in term of pitch, roll and yaw rate. A Simulink Dynamic Model of Aerostat-UAV from the previous project is simulated using MATLAB to compare with the actual dynamic behavior of the drone. Parrot AR.Drone, a quadcopter equipped with six sensors was used to collect the flight data.